2022
DOI: 10.1111/bjh.18113
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic factors in acute myeloid leukaemia with double‐mutated CCAAT/enhancer‐binding protein alpha (CEBPAdm)

Abstract: Summary The prognostic factors to stratify acute myeloid leukaemia (AML) with double‐mutated CCAAT/enhancer‐binding protein alpha (CEBPAdm) into different risk groups remains to be determined. In this retrospective study, we evaluated 171 consecutive patients with newly diagnosed AML with CEBPAdm by a Cox proportional hazards regression model. In univariate analyses, colony stimulating factor 3 receptor (CSF3R) and Wilms tumour 1 (WT1) mutations were associated with poor relapse‐free survival (RFS). The induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our previous studies have found that induction regimens including homoharringtonine and intermediate-dose cytarabine produced favorable outcomes in AML patients with CEBPA dm . [17][18][19] Given the relationship between immunophenotypes and the CEBPA mutation status, a scoring system was developed to identify AML with CEBPA-WHO based on immunophenotype and validated it internally and externally with good clinical performance. With this scoring system, we could preemptively identify AML patients with CEBPA WHO and choose an optimal induction regimen for them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have found that induction regimens including homoharringtonine and intermediate-dose cytarabine produced favorable outcomes in AML patients with CEBPA dm . [17][18][19] Given the relationship between immunophenotypes and the CEBPA mutation status, a scoring system was developed to identify AML with CEBPA-WHO based on immunophenotype and validated it internally and externally with good clinical performance. With this scoring system, we could preemptively identify AML patients with CEBPA WHO and choose an optimal induction regimen for them.…”
Section: Discussionmentioning
confidence: 99%
“…Induction therapies affect the clinical outcomes of AML with CEBPA mutation, either. Our previous studies found that the induction regimen including both homoharringtonine and intermediate‐dose cytarabine produced more favorable outcomes in AML patients with CEBPA dm with 3‐year RFS and OS at 84.7% and 92.8%, respectively, compared to the conventional cytarabine and daunorubicin regimen (3‐year RFS 27.7%, p < 0.001; and 3‐year OS 56.4%, p = 0.005) 17–19 . We are conducting a prospective clinical trial to confirm the efficacy of this regimen in patients with CEBPA dm AML (NCT04415008 at http://www.clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Accordingly, CEBPA dm AML has been recognized as a separate entity in the 2016 World Health Organization (WHO) Classification (WHO-2016) [ 12 ] and a favorable-risk category in 2017 European LeukemiaNet (ELN) recommendations. Concomitant WT1 mutations or CSF3R mutations helped predict a poor prognosis in patients with CEBPA dm [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Initially, CEBPAdm was stratified into favorable risk group. [4][5][6][7] Recently, studies demonstrated that the presence of inframe bZIP mutations of CEBPA was associated with favorable prognosis in newly diagnosed AML 2,8,9 which was updated in the new International Consensus Classification (ICC) of Myeloid Neoplasms and Acute Leukemia. 10 However, CEBPAdm without bZIP region mutation (CEBPAdmnonbZIP) is classified as CEBPA mutated AML in the 5th edition of WHO Classification of Haematolymphoid Tumours 11 but not in ICC classification.…”
Section: Introductionmentioning
confidence: 99%